Andrzej Wierzbicki, Rosja: etniczność i polityka, Oficyna Wydawnicza ASPRA JR, Warszawa 2011, ss. 340. - BODIO, Tadeusz (Przegląd Politologiczny, 2018)
Andrzej Wierzbicki, Rosja: etniczność i polityka, Oficyna Wydawnicza ASPRA JR, Warszawa 2011, ss. 340.